First insights from a mobile honeypot - Matthias Wählisch and Sebastian Trapp and Christian Keil and Jochen Schönfelder and Thomas C. Schmidt and Jochen Schiller (Association for Computing Machinery. Special Interest Group on Data Communication, 2012)
Computer systems are commonly attacked by malicious transport contacts. We present a comparative study that analyzes to what extent those attacks depend on the network access, in particular if an adversary targets specifically on mobile or non-mobile devices. Based on a mobile honeypot that extracts first statistical results, our findings indicate that a few topological domains of the Internet have started to place particular focus on attacking mobile networks.
Keywords: Mobile vs. non-mobile attacks; mobile honeypot